Implementasi Sistem Pembayaran Digital Berbasis Qris dalam Permberdayaan UMKM di Kelurahan Junti, Kab Serang - Eka Lailita Eti Varina; Wijar Algifari; Muhammad Ammar Hafizh; Riyan Fauzi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Advances in digital technology in the financial sector have encouraged Micro, Small, and Medium Enterprises (MSMEs) to shift from cash payment systems to non-cash payments through QRIS (Quick Response Code Indonesian Standard) as an effort to increase efficiency and modernize transactions. This research is motivated by the low level of QRIS adoption among MSMEs in Junti Village, Jawilan District, Serang Regency, Banten, most of which still rely on cash-based transactions. The purpose of this research is to analyze the implementation of QRIS by MSMEs, identify the obstacles faced, and assess the impact of the system's implementation on daily business activities. Data were collected through field observations, interviews with MSME actors, and supporting documentation, and this research was conducted in Junti Village in July 2025. The results revealed that some MSMEs that have adopted QRIS experienced benefits in the form of ease in conducting transactions, increased efficiency, and a more professional business image. These findings also confirm that the use of QRIS contributes to the acceleration of digital transformation in the MSME sector, although not yet fully optimal. The main obstacles encountered were limited access and the quality of internet infrastructure, which is still uneven, making it difficult for some business actors to utilize QRIS optimally. Based on these results, the study recommends the importance of increasing the intensity of socialization and training on QRIS use, as well as the need for ongoing support from local governments and financial institutions so that MSMEs can adapt more quickly and comprehensively to changes in digital technology, so that MSME digital transformation can take place effectively, inclusively, and sustainably. This study recommends the need for increased socialization, training, and support from financial institutions and local governments to encourage sustainable digital transformation of MSMEs.